2013
DOI: 10.1021/la401664y
|View full text |Cite
|
Sign up to set email alerts
|

Soy Protein/Soy Polysaccharide Complex Nanogels: Folic Acid Loading, Protection, and Controlled Delivery

Abstract: In this study, we developed a facile approach to produce nanogels via self-assembly of folic acid, soy protein, and soy polysaccharide. High-pressure homogenization was introduced to break down the original aggregates of soy protein, which benefits the binding of soy protein with soy polysaccharide and folic acid at pH 4.0. After a heat treatment that causes the soy protein denaturation and gelation, folic acid-loaded soy protein/soy polysaccharide complex nanogels were fabricated. The nanogels have a polysacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(50 citation statements)
references
References 47 publications
5
45
0
Order By: Relevance
“…[1][2][3][4][5] Their distinct properties including permeable structure, high water content, excellent stability, and multiple functionality have attracted broad interest across multidisciplinary areas of nanotechnology and biotechnology. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Recently, several sophisticated strategies have been developed to address the challenges for use of nanogels as clinical multifunctional biomaterials. [21][22][23] From a synthetic point of view, nanogels have been prepared either by cross-linking of functionalized responsive ones cannot be used for nanogel synthesis, thus limiting the choice of constituent polymers for nanogels.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Their distinct properties including permeable structure, high water content, excellent stability, and multiple functionality have attracted broad interest across multidisciplinary areas of nanotechnology and biotechnology. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Recently, several sophisticated strategies have been developed to address the challenges for use of nanogels as clinical multifunctional biomaterials. [21][22][23] From a synthetic point of view, nanogels have been prepared either by cross-linking of functionalized responsive ones cannot be used for nanogel synthesis, thus limiting the choice of constituent polymers for nanogels.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, cell uptake studies indicated that the cellular uptake for FA/SPI nanoparticles was greater than for SPI nanoparticles, particularly, at the end of a 24‐hour period, where uptake was 93% higher compared to SPI nanoparticles . Ding et al prepared nanogels of soy protein/soy polysaccharide as a carrier for folic acid. The nanogels were made by forcing high pressure homogenization for breaking down soy aggregates to bind to the polysaccharide compounds at pH 4 and by then applying heat treatment to enforce soy protein gelation.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Drug delivery nanoparticle systems are being increasingly applied to fields outside of medicine, including delivery of nutrients [14,91,92]. Folate is an essential nutrient that is not produced by the human body and, thus, is a dietary requirement.…”
Section: Polysaccharide-protein Nanoparticles For Delivery Of Folic Acidmentioning
confidence: 99%
“…Additionally, heat, oxygen, and light can result in degradation of folic acid during food processing and storage. Ding and Yao [14] prepared folic acid-loaded soy protein/soy polysaccharide nanogels that stabilized folic acid under acidic conditions and released it rapidly at neutral pH (similar to that in the intestine). The protein, polysaccharide, and folic acid were mixed in pH4 water and subjected to high-pressure homogenization.…”
Section: Polysaccharide-protein Nanoparticles For Delivery Of Folic Acidmentioning
confidence: 99%
See 1 more Smart Citation